Effect of topical papaverine on parathyroid function preservation after total thyroidectomy: a retrospective cohort study - Li, Jie; Li, Binbin; Hou, Binxin; Wang, Yinqin; Shi, Xiaonuo; Yan, Ying; Duan, Wenhao; Zheng, Shouhua (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the effectiveness of locally applied papaverine in preventing hypoparathyroidism after total thyroidectomy and its impact on parathyroid hormone (PTH) recovery.Study designRetrospective cohort study.SettingThe First Affiliated Hospital of Zhengzhou University.MethodsThis single-center retrospective cohort study involved 226 patients who underwent total thyroidectomy at the First Affiliated Hospital of Zhengzhou University from March 2023 to March 2025. The incidence of hypoparathyroidism on postoperative day 1 and the PTH recovery rate within 30 days afterward are compared between patients who received papaverine and those who did not. Data analysis uses the independent samples t-test, the Mann-Whitney U test, and the χ² test.ResultsPatients are divided into two groups: those who received intraoperative papaverine (n = 106) and a control group (n = 120). On postoperative day 1, hypoparathyroidism occurs in 40% of the papaverine group and 53% of the control group, respectively. Postoperative PTH recovery rates gradually increase over time, with significantly higher rates in the papaverine group compared to the control group on days 3, 5, and 30.ConclusionApplying papaverine directly during surgery effectively lowers the risk of early hypoparathyroidism after total thyroidectomy while promoting faster PTH recovery. This method is simple, easy to perform, and has a high safety profile. Future multicenter randomized controlled trials should be conducted to confirm long-term effectiveness and refine the dosing protocol.